Analysis of storage conditions of a wheat silo-bag for different weather conditions by computer simulation - Arias Barreto, Alien (2013)
A validated mathematical model was used to analyse grain storage condition and determine the change in concentration of CO2 in a silo-bag holding wheat from summer to winter for a typical productive region with sub-tropical (Saenz Peña, Chaco Province), intermediate (Pergamino, Buenos Aires Province) and temperate weather conditions (Balcarce, Buenos Aires Province) in Argentina. Initial moisture content of grain was set to 12, 14 and 16% w.b and bagging temperatures to 25 °C and 40 °C. For base conditions (12% w.b; 25 °C) CO2 level increased to 4% V/V and O2 decreased to 15.5% V/V in Balcarce while in Saenz Peña CO2 level increased to 6% V/V and O2 decreased to 13.9% V/V. For wet grain (16% w.b; 25 °C and 40 °C), O2 depleted to less than 1% V/V at the three locations. The grain mean temperature in combination with the CO2 and O2 levels achieved in the silo-bags demonstrate that, for the climatic conditions of southern and central regions of Argentina, insect control is feasible in silo-bags. Mean dry matter loss for all the storage conditions was estimated and compared to the critical limit for safe storage of grain and seeds; it did not exceed limits that would reduce commercial quality, although seed could be affected when stored wet and during the summer.